Prevalence and risk factors associated with Campylobacter spp. and Salmonella enterica in livestock raised on diversified small-scale farms in California. (12th December 2019) - Pires, A. F. A.; Patterson, L.; Kukielka, E. A.; Aminabadi, P.; Navarro-Gonzalez, N.; Jay-Russell, M. T.
Abstract: Diversified farms are operations that raise a variety of crops and/or multiple species of livestock, with the goal of utilising the products of one for the growth of the other, thus fostering a sustainable cycle. This type of farming reflects consumers' increasing demand for sustainably produced, naturally raised or pasture-raised animal products that are commonly produced on diversified farms. The specific objectives of this study were to characterise diversified small-scale farms (DSSF) in California, estimate the prevalence of Salmonella enterica and Campylobacter spp. in livestock and poultry, and evaluate the association between farm- and sample-level risk factors and the prevalence of Campylobacter spp. on DSSF in California using a multilevel logistic model. Most participating farms were organic and raised more than one animal species. Overall Salmonella prevalence was 1.19% (95% confidence interval (CI95 ) 0.6–2), and overall Campylobacter spp. prevalence was 10.8% (CI95 = 9–12.9). Significant risk factors associated with Campylobacter spp. were farm size (odds ratio (OR)10–50 acres: less than 10 acres = 6, CI95 = 2.11–29.8), ownership of swine (OR = 9.3, CI95 = 3.4–38.8) and season (ORSpring: Coastal summer = 3.5, CI95 = 1.1–10.9; ORWinter: Coastal summer = 3.23, CI95 = 1.4–7.4). As the number of DSSF continues to grow, evaluating risk factors and management practices that are unique to these operations will help identify risk mitigation strategies and develop outreach materials to improve the food safety of animal and vegetable products produced on DSSF.